Domino hydroformylation‐Wittig reactions - Breit, Bernhard; Zahn, Stephan K. (Angewandte Chemie. International edition, 1999)
Abstract Methallyl and homomethallyl alcohols can undergo stereoselective hydroformylation-Wittig and hydroformylation-Wittig-hydrogenation reactions in one-pot domino processes. This sequential transformation allows the formation of C-C bonds and the generation of a new stereogenic center, and gives preparatively interesting compounds [Eq. (a)]. The reaction products are obtained in satisfactory to good yields and in diastereoselectivities of 90:10 to >98:2. CDG=catalyst-directing group; R'=H; R''=OEt, Me.